Juvenile plumage whiteness is associated with the evolution of clutch size in passerines. (30th April 2019) - Morales, Judith; Cuervo, José Javier; Moreno, Juan; Soler, Juan José
Abstract: The offspring of many animals are conspicuous during parental dependence, despite juveniles generally suffering from high predation risk. However, to date, it is unclear whether offspring structural ornaments play a role in intrafamily communication. This is the case of conspicuous plumage in young birds, which is worn unchanged during a long period after fledging, when they still depend on their parents. If plumage color facilitates intrafamily interactions, its role should be more important in large-brooded species, where the strength of intrafamily conflict is potentially stronger. We therefore performed a comparative study in 210 passerine bird species to test whether an offspring structural trait, white plumage, evolves more frequently in lineages with larger clutches. We also explored the number of broods raised per year as another source of intrafamily conflict. First, we found that juvenile whiteness was more frequent in open-nesting species. Moreover, in agreement with our prediction, the presence of juvenile white tail/wing patches was strongly and positively associated with clutch size. This relationship was not due to the strong resemblance between offspring and adult plumage, which was controlled for in the statistical analyses. Moreover, the association remained significant after taking into account predation risk, for which there was information for a subset of species. In contrast, juvenile whiteness was not associated with the number of broods raised per year. These results may suggest that the evolution of juvenile conspicuousness is favored in species with potentially stronger intrabrood sibling conflict. Abstract : The presence of conspicuous white feathers in young birds is more common in passerine lineages with larger clutches, even after controlling for predation risk. Assuming that white feathers may function as signals in intrafamily communication, this finding suggests that offspring conspicuousness is more common in those species with a more complex social network and with higher potential for intrafamily conflict.